2020
DOI: 10.3390/biom10081104
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Export from Neurons and Multi-Kinase Signaling Cascades Contribute to Ouabain Neuroprotection in Hyperhomocysteinemia

Abstract: Pathological homocysteine (HCY) accumulation in the human plasma, known as hyperhomocysteinemia, exacerbates neurodegenerative diseases because, in the brain, this amino acid acts as a persistent N-methyl-d-aspartate receptor agonist. We studied the effects of 0.1–1 nM ouabain on intracellular Ca2+ signaling, mitochondrial inner membrane voltage (φmit), and cell viability in primary cultures of rat cortical neurons in glutamate and HCY neurotoxic insults. In addition, apoptosis-related protein expression and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…At present, more and more studies have found that some cardiotonic steroid drugs also show significant pharmacological activities in neurological diseases. For example, CTS are involved in psychophysiological processes such as regulation of mental symptoms and protection of nerve cells through the regulation of neurotransmitters and homocysteine (HCY) (Sibarov et al, 2012;Lopachev et al, 2019;Ivanova et al, 2020).…”
Section: Pharmacological Activity Of Cts In Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, more and more studies have found that some cardiotonic steroid drugs also show significant pharmacological activities in neurological diseases. For example, CTS are involved in psychophysiological processes such as regulation of mental symptoms and protection of nerve cells through the regulation of neurotransmitters and homocysteine (HCY) (Sibarov et al, 2012;Lopachev et al, 2019;Ivanova et al, 2020).…”
Section: Pharmacological Activity Of Cts In Nervous Systemmentioning
confidence: 99%
“…Therefore, the control of nerve damage caused by HCY is an important means to prevent the occurrence of cerebrovascular diseases and alleviate the symptoms of Parkinson's disease and Alzheimer's disease. HCY-induced neurodegeneration is caused by neuronal permanent plasma membrane depolarization and cytosolic Ca 2+ overload of neurons, known as excitotoxic stress (Ivanova et al, 2020). Studies have found that ouabain can effectively antagonize neuronal damage caused by high HCY (Ivanova et al, 2020).…”
Section: Study On the Effect Of Cts On Hcymentioning
confidence: 99%
“…Redox modulation of cysteine residues is one of the post-translational modifications of NMDAR. HCY accumulation in the human plasma, known as hyperhomocysteinemia, can exacerbate neurodegenerative diseases and act as a persistent NMDAR agonist (Ivanova M. et al, 2020). Meanwhile, HCY activates GluN2 subunit-dependent redox regulation of NMDAR by the reduction of NMDAR disulfide (Sibarov et al, 2020).…”
Section: Influence Of Related Proteins and Signaling Pathways On Nmdarmentioning
confidence: 99%
“…It is well established that HCY activates N-methyl-d-aspartate receptors (NMDARs) [10,11] and group I metabotropic receptors [12,13]. The NMDAR activation by HCY and related intracellular calcium accumulation is thought to provide a major contribution to the HCY neurotoxicity [11,14,15]. NMDARs represent tetramer protein complexes composed of two GluN2 subunits, which form an agonist binding site for endogenous amino acids glutamate and HCY, and two GluN1 subunits bearing co-agonist binding sites for glycine [16] or d-serine [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…HCY activates the GluN1/2A subtype of NMDARs with the highest affinity among NMDARs but provokes desensitization of GluN1/2B receptors [19]. This is a pharmacological feature determining the GluN2A-subunit dependence of the HCY neurotoxicity [15,[20][21][22][23]. NMDAR competitive antagonist (AP-5) and channel blockers (MK-801 and memantine) prevent HCY-induced neuronal damage both in vitro [7,11] and in vivo [24] during mild and intermediate hyperhomocysteinemia.…”
Section: Introductionmentioning
confidence: 99%